Corporate Governance and firm Characteristics on Intellectual Capital Disclosure - Isnaeni, Yuni; Sari, Nadia Kurnia Novita; Hammed, Rizgar (Journal of Accounting and Finance, 2026)
Purpose – This study aims to examine the effect of leverage, independent commissioners, ownership concentration, and firm age on Intellectual Capital Disclosure (ICD). Design/methodology/approach – This research employs a quantitative approach using secondary data obtained from annual reports of transportation & logistics and healthcare companies listed on the Indonesia Stock Exchange during 2021–2024. The sample consists of 45 firms with 180 firm-year observations selected using purposive sampling. Panel data regression analysis is applied, and model selection is conducted through Chow, Hausman, and Lagrange Multiplier tests. Data are processed using EViews. Findings – The results indicate that leverage has a negative effect on ICD, suggesting that higher debt levels tend to reduce voluntary disclosure of intellectual capital. Independent commissioners have a positive effect on ICD, indicating that effective board monitoring enhances transparency of intangible assets. Ownership concentration shows no significant effect on ICD. Firm age has a positive effect on ICD, implying that more experienced firms possess more mature disclosure practices. Research limitations/implications – This study is limited to two sectors and a four-year observation period. Future research may expand sector coverage, extend the period, or include additional governance variables. JEL : G34, M41